Sustainable Tourism Development Strategy in Tanjung Puting National Park from an Environmental Economics Perspective - Abdul Halim; Dicky Perwira Ompusunggu; Dimas Prima Yosa (AIBPM Publisher, 2025)
Tourism in Tanjung Puting National Park (TNTP) holds significant economic and ecological potential; however, increasing tourist visits also place pressure on environmental quality and wildlife habitats, requiring sustainable management strategies. This study aims to identify sustainable tourism development strategies in TNTP from an environmental economics perspective through a systematic literature review. The study reviewed 30 scientific publications published between 2021 and 2025 related to sustainable tourism, environmental economic valuation, community participation, and conservation governance. The findings indicate that zoning policies and visitor capacity restrictions effectively reduce environmental degradation in the park. Community participation through Community-Based Tourism programs has increased local welfare by approximately 22–35% while strengthening compliance with conservation practices. Furthermore, the economic valuation of ecosystem services in TNTP shows high potential value, although it has not been fully integrated into conservation funding mechanisms. The study concludes that integrating environmental economic policies, strengthening community capacity, and developing ecosystem service–based conservation financing are crucial for achieving sustainable tourism development in TNTP